In search of solvency: changing agricultural governance in an ethnic minority autonomous region of southwest China. (9th August 2007) - Li, Yongxiang; Tilt, Bryan
During the last quarter century, China's agricultural sector has undergone a dramatic transformation from collective to private production, resulting in marked improvements in quality of life for most rural citizens. However, economic development in the countryside has been highly uneven, particularly in China's southwestern region, with its arid land, rugged topography and high concentration of ethnic minority populations. Based on recent ethnographic research, this paper discusses the innovative governance strategies used by a state-owned sugar mill in a rural township in the southwestern province of Yunnan in order to survive within a changing economic environment. We argue that, despite economic liberalisation, the state ? particularly at the local level ? still plays a key role in mediating between farmers and the marketplace. The implications of this shifting governance structure for agricultural development in poor, minority areas and for China's nearly 800 million peasants are discussed.